PERAN DUNIA USAHA BAGI SMK UNTUK MENINGKATKAN KUALITAS LULUSAN - Ade Chairunnisa Gultom (Universitas Negeri Medan, 2015)
ABSTRACT The concept that offers a close cooperation between vocational, community and government with their respective responsibilities, the evolved based on a wish granting independence to the school to get involved actively and dynamically in the context of the process of improving the quality of education through the management of existing school resources. Schools must be able to translate and capture the essence of the macro policies of education and understanding of environmental conditions (pros and cons) and then through the planning process, the school must formulate into micro policies in the form of priority programs to be implemented and evaluated by the school in accordance with the vision and their mission - each. Schools should determine the quality targets for the next year. Thus iuris school but still within the terms of reference of national policy and supported with the provision of adequate inputs, has responsibility for the development of its resources in accordance with the learning needs of students and society. The diversity of environmental conditions varied needs of schools and students in the learning process coupled with the geography of Indonesia is very complex, often can not be fully appreciated by a central bureaucracy. Therefore, in the process of improving the quality of education necessary to find an alternative school management. This prompted the birth of the concept of school -based management of quality improvement. Management of these alternatives provide independence for the school to organize themselves in order to improve the quality of education , but still refers to the national policy. Kata Kunci : Kualitas lulusan SMK dan Dunia Usaha/Industri